Design and integration of PC-based modularised CAM manufacturing package - Rosman Aziz. (2009)
The process of cam design is complex and mathematically involved. Many factors need to be considered during the design stage. Among these are factors such as the motion specifications, the type of cam and follower to be used, the mode of follower movement, the space constraint, the effects of pressure angle and radius of curvature, and the type and magnitude of loading to be resisted by the cam and follower surfaces.